Indonesian middle class as cultural intermediaries, ‘running’ for trendy urban lifestyle - Dwianto, Raphaella Dewantari; Rahardini, Armita (Kasetsart Journal of Social Sciences, 2021)
Running in Indonesia has been considered as an easy, cheap and inclusive sport. Focusing on running among Indonesian urban middle class, this research found that before the COVID-19 pandemic hit, there were hundreds of urban runner communities and more than one hundred running competitions held during the last decade. While previous studies on sport focused more on socio-demographic factors as the cause of sport participation, this article argues on the significance of urban middle-class as the cultural intermediaries who popularize running into lifestyle, based on the analysis of three dimensions: framing, expertise, and impact. Running has become urban lifestyle through redefinition and commodification by the middle class themselves with the help of social media, thus creating urban middle-class characteristics. Not only does the urban middle class accumulate cultural capital resulting from the legitimacy as the expert of recreational sport, but it also gains social identity as member of modern urban society.